Faculty's perspectives on undergraduate Islamic education students' practice of critical thinking skills - Margatama, Pandang (Kulliyyah of Education, International Islamic University Malaysia, 2021)
The implementation of critical thinking skills is important for students. Previous studies have found that the educational institutions in Malaysia are still unable to achieve the objectives of instructional pedagogy in the classroom especially in enhancing critical thinking skills. Therefore, this study examined how to develop critical thinking skills of undergraduate students from the perspective of faculty’s members. This study was qualitative in nature because it sheds light on the experiences and perceptions of individuals from their own perspectives on a particular program. The data collection was carried out through interviews with faculty members, who teach the teaching of Islamic Education undergraduate students, Kulliyyah of Education, IIUM. Based on the themes that emerged from the data, three conclusions were drawn. Firstly, the participants highlighted that the practice of critical thinking skills would leave a positive impact on the learning experience of students. Their responses suggest that critical thinking skill is the ability of the student to collect information and express his/her thought to solve problems. Likewise, through the acquisition of higher order thinking skills, problem solving skills, reflection skills and synthesise skills, students are able to practice critical thinking skills. Secondly, among the effective strategies in developing critical thinking skills of Islamic Education students, students’ centred learning activity, visual learning, and assignment, workshops, building self-confidence and open-ended questions. Students are able to develop critical thinking skills through the implementation of these effective strategies. Although the practice of critical thinking skills has been implemented, there will also obstacles in developing critical thinking skills related to problem solving skills issues, higher ordered thinking issues, lack of confidence, language skills issues, close mindedness, time management skill issues, academic background of the students and students’ family background. The study suggests carrying out further researches which can cover a greater population especially in the Kulliyyah of Education, IIUM. It also recommends supporting the management educational institutions in conducting programs to develop the critical thinking skills of the students.